Respostas

2013-10-24T17:07:28-02:00
X² - 6x + 5x - 30 = 51 - x
x² - 6x + 5x - 30 - 51 + x = 0
x² + 0 - 81 = 0
x² - 81 = 0
D = Delta
D = b² - 4ac
D = 0² - 4 * 1 * (- 81)
D = 324

x = - b + raiz² de D 
-------------------------------
             2a

x = - 0 + raiz² de 324
-------------------------------
            2 * 1

x = - 0 + 18
      ------------
           2

x' = - 0 + 18 
           2
x' = 18 
       2
x' = 9

x" = - 0 - 18 
           2
x" = - 18 
         2
x" = - 9

Resposta = (9, -9)